Distributed Temperature Sensing to Measure Infiltration Rates Across a Groundwater Recharge Basin. Issue 6 (8th May 2020) - Medina, Ricardo; Pham, Christine; Plumlee, Megan H.; Hutchinson, Adam; Becker, Matthew W.; O'Connell, Patrick J.
Abstract: Managed aquifer recharge is used to augment groundwater resources and provide resiliency to water supplies threatened by prolonged droughts. It is important that recharge facilities operate at their maximum efficiency to increase the volume of water stored for future use. In this study, we evaluate the use of distributed temperature sensing (DTS) technology as a tool to measure high‐resolution infiltration rates at a large‐scale recharge facility. Fiber optic cable was laid out inside a spreading basin in a spiral pattern, at two different depths. The cables measured the propagation of diurnal surface water temperature oscillations into the basin depth. The rate of heat propagation is proportional to the velocity of the water, making it possible to estimate the infiltration rate from the temperature measurements. Our results showed that the infiltration rate calculated from DTS, averaged over the entire basin, was within 5% of the infiltration rate calculated using a conventional metering method. The high‐resolution data obtained from DTS, both spatially and temporally, revealed heterogeneous infiltration rates throughout the basin; furthermore, tracking the evolution of infiltration rates over time revealed regions with consistently high infiltration rates, regions with consistently low infiltration rates, and regions that evolved from high to low rates, which suggested clogging within that region. Water utilities can take advantage of the high‐resolution information obtained from DTS to better manage recharge basins and make decisions about cleaning schedule, frequency, and extent, leading to improved basin management strategies, reduced O&M costs, and increased groundwater recharge. Abstract : Article impact statement : DTS technology can improve the management of spreading basins by providing spatial distribution of infiltration rates over time.